The First Russian Rhetorical Guidance in Political Oratory (On M. N. Popov’s Book “Political eloquence. What a speaker needs”) - S. A. Gromyko (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The book “Political eloquence. What a speaker needs” by M. N. Popov is analyzed. The book is considered as the first Russian rhetorical guide to political speech. The appearance of Popov’s work is associated with the birth of parliamentary and - more broadly - political rhetoric in Russia in the early 20th century. Particular attention is paid to the format of the publication - public, popular rhetorical guidance - and its content in terms of the author’s ideas about the emerging parliamentary communication. A portrait of a reader is recreated: this is a person who does not have a systematic education, but has experience in pronouncing non-institutional speeches at rallies and gatherings. The structure of the book in the aspect of traditional rhetorical guides is analyzed. Attention is drawn both to the deviations from the traditional canons of compiling a textbook on rhetoric, and to the continuity of the latter. Particular attention is paid to M. N. Popov’s usage of psychological approach in explaining the problems of interaction between the speaker and the audience. It is concluded that M. N. Popov’s book reflects largely idealistic views about oral public speech in Parliament, but at the same time anticipates many traits of domestic parliamentary communication. Analyzed work is of scientific interest as a source of study of the history of Russian rhetoric reflecting the rhetorical ideal of the Russian public political speech.